2019
DOI: 10.1590/s1983-41952019000600004
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-based calibration of Brazilian structural design codes used in the design of concrete structures

Abstract: ResumoThis paper presents a reliability-based calibration of partial safety factors for Brazilian codes used in the design of concrete structures. The work is based on reliability theory, which allows an explicit representation of the uncertainties involved in terms of resistances and loads. Regarding the resistances, this study considers beams with concrete of five classes (C20, C30, C40, C50 and C60), three ratios between base and effective depth (0.25, 0.50 and 0.75), three longitudinal reinforcement ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…The few existent reliability assessments for structures in Brazil (Beck and Souza Júnior [32]; Santos et al [33],) demonstrated annual failure probabilities ranging from -4 2.15 × 10 to -8 6.80 × 10 , encompassing the two target values adopted herein. Recent reliability-based calibration studies for the Brazilian codes ( [32]; Santiago et al [34]; Santiago et al [35],) adopted -5 2.7 × 10 for the target annual failure probability, which is in fair agreement with the lower bound investigated in this paper. The inferior bound is also consistent with international standards for acceptable individual risk of fatality due to structural failure, a probability of -6 10 per year for low seismicity regions [11].…”
Section: Risk-targeting Methodologysupporting
confidence: 85%
“…The few existent reliability assessments for structures in Brazil (Beck and Souza Júnior [32]; Santos et al [33],) demonstrated annual failure probabilities ranging from -4 2.15 × 10 to -8 6.80 × 10 , encompassing the two target values adopted herein. Recent reliability-based calibration studies for the Brazilian codes ( [32]; Santiago et al [34]; Santiago et al [35],) adopted -5 2.7 × 10 for the target annual failure probability, which is in fair agreement with the lower bound investigated in this paper. The inferior bound is also consistent with international standards for acceptable individual risk of fatality due to structural failure, a probability of -6 10 per year for low seismicity regions [11].…”
Section: Risk-targeting Methodologysupporting
confidence: 85%
“…The random variables are presented in Table 6, where some of them are Brazilian statistics, as reported by Santiago [25], [26] and Santiago et al [47], [48]. Other variables consider the statistics utilized in Nowak [27] and Wassef et al [8].…”
Section: Reliability Indexesmentioning
confidence: 99%
“…Even allowing this reduction, the standard 12 still maintains the quantification of safety based on partial safety factors. Some authors [15][16][17][18] have been concerned with the partial coefficients defined by the standards since they do not reflect the absolute safety that the bridge presents, which could cause the structural verification to reach conclusions that do not correspond to reality.…”
Section: Introductionmentioning
confidence: 99%